Evaluation of the Character Education Strengthening Program in Elementary Schools in View from CIPP (Context, Input, Process, Product) - Silfanny, Hilda; Mustika, Dea (Universitas Pendidikan Mandalika, 2024)
This research aims to evaluate the context, input, process, and products in the character education strengthening program at SD Muhammadiyah 05 Pekanbaru. The approach used in this research was qualitative with descriptive methods. Data collection techniques were carried out through observation, interviews, and documentation. Meanwhile, data analysis techniques included reduction, data presentation, and drawing conclusions. The results of this research showed that the character education program at SD Muhammadiyah 05 Pekanbaru had proven to be effective. This can be seen from several aspects: First, the context aspect, where most of it has been fulfilled well. Program procedures, which include a clear and detailed vision, mission, goals, and background, were in accordance with community needs. It is evidenced by the increasing number of students studying and student participation in extracurricular activities, as well as student enthusiasm in carrying out character education programs. Second, is the input aspect, where most of the input components have been fulfilled properly. The majority of teachers implemented character education programs effectively. Third, the process aspect, where all components had been implemented quite well. This can be seen from the value of students' discipline and curiosity, as well as the enthusiasm of educators in guiding and directing students in implementing character education, both in the classroom and outside the classroom. Fourth, the product aspect, where most of the product components of the character education program at SD Muhammadiyah 05 Pekanbaru had shown satisfactory results. This can be seen from the instillation of character values carried out, as well as the implementation or habituation of character education carried out by each student in activities at school. Apart from that, the achievements achieved, both in the academic and non-academic fields, also showed the success of this program.